Effects of compost as a soil amendment on bacterial community diversity in saline–alkali soil - Xu, Daolong; Yu, Xiaowen; Chen, Jin; Li, Xiufen; Chen, Jian; Li, JiangHua (Frontiers in Microbiology, 2023)
Soil salinization poses a worldwide challenge that hampers agricultural productivity. Employing high-throughput sequencing technology, we conducted an investigation to examine the impact of compost on the diversity of bacterial communities in saline soils. Our study focused on exploring the diversity of bacterial communities in the inter-root soil of plants following composting and the subsequent addition of compost to saline soils. Compared to the initial composting stage, Alpha diversity results showed a greater diversity of bacteria during the rot stage. The germination index reaches 90% and the compost reaches maturity. The main bacterial genera in compost maturation stage are Flavobacterium, Saccharomonospora, Luteimonas and Streptomyces. Proteobacteria, Firmicutes, and Actinobacteria were the dominant phyla in the soil after the addition of compost. The application of compost has increased the abundance of Actinobacteria and Chloroflexi by 7.6% and 6.6%, respectively, but decreased the abundance of Firmicutes from 25.12% to 18.77%. Redundancy analysis revealed that soil factors pH, solid urease,organic matter, and total nitrogen were closely related to bacterial communities. The addition of compost effectively reduced soil pH and increased soil enzyme activity and organic matter content. An analysis of this study provides theoretical support for compost's use as a saline soil amendment.